Comparing efficacy of first-line treatment of metastatic castration resistant prostate cancer: a network meta-analysis of randomized controlled trials - Liu, Yang; Deng, Xianzhong; Wen, Zhi; Huang, Jing; Wang, Chongjian; Chen, Caixia; Bao, Erhao; Wang, Jiahao; Yang, Xuesong (Frontiers in Pharmacology, 2023)
Abstract Background: Metastatic castration-resistant prostate cancer (mCRPC) presents significant treatment selection challenges due to limited therapeutic options. This study aimed to comprehensively assess the efficacy of multiple treatment regimens for mCRPC through a network meta-analysis (NMA) of randomized controlled trials (RCTs). Methods: A systematically comprehensive search for randomized controlled trials (RCTs) was performed in Pubmed, Cochrane Library, Embase, and Web of Science databases. The network meta-analysis was employed to compare the overall survival (OS), progression-free survival (PFS), and radiographic progression-fre survival (rPFS) among different interventions at specific time points. This study was prospectively registered with PROSPERO (CRD42023422823). Results: A total of 29 RCTs, involving 12706 patients and investigating 16 interventions, were included in the analysis. Chempretarget ((capivasertib or cabozantinib) + docetaxel + prednisone)) and PARP (Olaparib or rucaparib) inhibitors emerged as interventions that significantly improved survival outcomes compared to first-line treatment in mCRPC patients. Chempretarget demonstrated superior overall survival starting from the 12th month, while PARP inhibitors showed a clear advantage in progression-free survival within the 3-18 month range. Notably, chempre ((Docetaxel or Cabazitaxel) + prednisone) exhibited favorable performance in radiographic progression-free survival during the 3-18 month period. Conclusion: Our findings underscore the efficacy of chempretarget, PARP inhibitors, and chempre in enhancing survival outcomes for mCRPC patients. Further head-to-head comparisons are warranted to validate these results. These findings carry important implications for treatment decision-making in mCRPC and may guide the development of more effective therapeutic strategies.